2023
DOI: 10.1002/cplu.202300132
|View full text |Cite
|
Sign up to set email alerts
|

3‐Pyrrolyl BODIPY Based Schiff Base Fluorophores: A Selective Chemodosimetric and Optical Sensor for Diethyl Chlorophosphate

Abstract: Diethyl chlorophosphate (DCP), an organophosphate, is utilized as a pesticide, herbicide, and for various other applications. Despite many uses of organophosphates, the organophosphates are noxious and harmful substances, and their selective detection is a critical concern in the context of the environment, physiology, and social security. In a methodological quest, here we have synthesized two Schiff base compounds 1 and 2 by introducing the hydroxyl group at the α-position of 3-pyrrolyl BODIPY either directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…However, the LUMO and LUMO+1 orbitals for both 10 and 10·2H + showed a similar electron distribution on both a-pyrrolyl BODIPY units and the hydrazine linker along with some distribution on meso -tolyl groups as well. However, similar to other reported BODIPYs, 24–27 the meso -aryl group and BF 2 unit did not contribute to the frontier molecular orbitals in 10 and 10·2H + . In addition, the electron distribution of the LUMO of 10 has a large contribution on the hydrazine linker with good orbital overlap between imine N and C, supporting the electron transfer process from the hydrazine moiety to α -pyrrolyl BODIPY.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, the LUMO and LUMO+1 orbitals for both 10 and 10·2H + showed a similar electron distribution on both a-pyrrolyl BODIPY units and the hydrazine linker along with some distribution on meso -tolyl groups as well. However, similar to other reported BODIPYs, 24–27 the meso -aryl group and BF 2 unit did not contribute to the frontier molecular orbitals in 10 and 10·2H + . In addition, the electron distribution of the LUMO of 10 has a large contribution on the hydrazine linker with good orbital overlap between imine N and C, supporting the electron transfer process from the hydrazine moiety to α -pyrrolyl BODIPY.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the appended pyrrole of 3-pyrrolyl BODIPY is highly susceptible to functionalization at the α-position and the α-functionalized 3-pyrrolyl BODIPYs are very useful synthons to synthesize several interesting fluorescent 3-pyrrolyl BODIPY based conjugates. In due course of time, we 22–28 and others 29–31 have developed a simple method for the synthesis of 3-pyrrolyl meso -aryl BODIPY based derivatives and they have been used in fluorescence sensing, photodynamic therapy, biotechnology, bioimaging, light-harvesting systems, etc. We also developed a method 32 to remove BF 2 units from BODIPYs and the resulting ligands have been used in coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 3 was also treated with 2aminophenol in ethanol at reflux for 4 h followed by recrystallization to afford 3-pyrrolyl BODIPY-Schiff base compound 9 by our recent publication. 34 However, when 3 was reacted with o-phenylenediamine in ethanol at reflux for 4 h, it afforded α-benzimidazolyl 3-pyrrolyl BODIPY 10 in good yields. Compound 9 was reacted with [Ru(p-cymene)Cl 2 ] 2 in toluene at reflux followed by recrystallization to yield BODIPY-Ru(II) complex 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To prepare Ru­(II)-α-formyl 3-pyrrolyl BODIPY complex 6 , we first prepared the required ligand, α-formyl 3-pyrrolyl BODIPY 3 , by treating 3-pyrrolyl BODIPY 2 with POCl 3 in DMF/DCE under Vilsmeier-Haack reaction conditions. , Compound 3 was then treated with [Ru­( p -cymene)­Cl 2 ] 2 in toluene in the presence of a base at reflux for 3 h followed by recrystallization to afford Ru­(II)-α-formyl 3-pyrrolyl BODIPY 6 in 40% yield (Scheme ). Compound 3 was also treated with 2-aminophenol in ethanol at reflux for 4 h followed by recrystallization to afford 3-pyrrolyl BODIPY-Schiff base compound 9 by our recent publication . However, when 3 was reacted with o -phenylenediamine in ethanol at reflux for 4 h, it afforded α-benzimidazolyl 3-pyrrolyl BODIPY 10 in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…and these functionalized 3-pyrrolyl BODIPYs can be further derivatized to prepare several interesting fluorescent compounds for various applications. 6–10 Others 11–14 and we 3–10 have developed a simple route for synthesizing 3-pyrrolyl BODIPYs. We also showed that the BF 2 unit of 3-pyrrolyl BODIPYs could also be demasked by treating 3-pyrrolyl BODIPYs with Lewis acids such as AlCl 3 and ZrCl 4 to afford tripyrrolyl ligands that can be used to prepare interesting coordination complexes such as 3 .…”
Section: Introductionmentioning
confidence: 99%